A comparison of methods to suppress electrocardiographic artifacts in local field potential recordings. (February 2023) - Stam, M.J.; van Wijk, B.C.M.; Sharma, P.; Beudel, M.; Piña-Fuentes, D.A.; de Bie, R.M.A.; Schuurman, P.R.; Neumann, W.-J.; Buijink, A.W.G.
Highlights: The ability of three ECG artifact suppression methods to recover Parkinson's disease-related LFP signal features was compared. The use of external ECG recordings and artifact epoch length significantly influence ECG suppression performance. The singular value decomposition was found most suited for balancing the trade-off between artifact cleaning and signal loss. Abstract: Objective: Local field potential (LFP) recordings from deep brain stimulation (DBS) electrodes are often contaminated with electrocardiographic (ECG) artifacts that hinder the detection of disease-specific electrical brain activity. Methods: Three ECG suppression methods were evaluated: (1) QRS interpolation of the Perceive toolbox, (2) template subtraction, and (3) singular value decomposition (SVD). LFPs were recorded with the Medtronic Percept TM PC system in nine Parkinson's disease patients with stimulation OFF ("OFF-DBS"; anode disconnected) and ON at 0 mA ("ON-DBS 0 mA"; anode connected). Findings were verified with simulated ECG-contaminated time series. Results: ECG artifacts were present in 10 out of 18 ON-DBS 0 mA recordings. All ECG suppression methods drastically reduced artifact-induced beta band (13–35 Hz) power and at least partly recovered the beta peak and beta burst dynamics. Using external ECG recordings and lengthening artifact epoch length improved the performance of the suppression methods. Increasing epoch length, however, elevated the risk of flattening the beta peak and losing beta burst dynamics. Conclusions: The SVD method formed the preferred trade-off between artifact cleaning and signal loss, as long as its parameter settings are adequately chosen. Significance: ECG suppression methods enable analysis of disease-specific neural activity from signals affected by ECG artifacts.